Monitoring dan Evaluasi Rencana Induk Kelitbangan Kota Surakarta - Herri Widiyanto; Aris Setiawan; Rony Widjanarko; Wulan Aji Prabawaningrum (Badan Riset dan Inovasi Daerah Kota Surakarta, 2023)
Law Number 23 of 2014 concerning Regional Government as amended several times, most recently by Law Number 9 of 2015 stipulates that the research and development function is one of the supporting functions in the implementation of government affairs in the regions. This Hzl was then followed up through Government Number 18 of 2016 concerning Regional Apparatuses as amended by Government Regulation of the Republic of Indonesia Number 72 of 2019, which states that Regional Bodies are supporting elements of Government Affairs which are under the authority of Regency/City Regions. Supporting affairs as referred to in the article consist of (1) planning; (2) finance, (3) staffing and education and training; (4) research and development, and (5) other supporting functions in accordance with the provisions of the applicable laws and regulations.